Neumonía grave adquirida en la comunidad en pacientes pediátricos en un centro de alta complejidad en Cali, Colombia. - Paola Pérez-Camacho (Asociación Colombiana de Infectología, 2024)
Objective: Community-acquired pneumonia (CAP) is one of the leading causes of mortality in the pediatric population. It often leads to pediatric hospitalization, with children under 1-year-old being the most affected and usually requiring management in the intensive care unit. Recent molecular studies indicate that viruses are the most common etiology. The aim of our study was to characterize the pediatric population with severe CAP in a high complexity center in Cali, Colombia, describing demographics, etiologic factors, clinical evolution and outcomes of patients.Method: We conducted retrospective observational study in a private hospital of high-complexity. Ninety-three patients aged between 1 month and 18 years old with the diagnosis of severe CAP admitted to the Pediatric Intensive Care Unit (PICU) during a 5-year period (2015-2020) were included.Results: In our population there was no significant gender difference, our median age was 10 months (IQ 3-31), 77% presented respiratory distress and 48% requi-red invasive mechanical ventilation. The most commonly isolated microorganism was Respiratory Syncytial Virus (RSV) (n=36), followed by Rhinovirus/Enteroviruscomplex in 41% (n=21), and Metapneumovirus 12% (n=6). Viral pneumonia was the most common in our patients (44%, n = 41), followed by viral-bacterial co-infection (13.9%, n=13). Seven fatal cases were reported.Conclusions: Our study provides epidemiologic evidence of microorganisms that cause severe CAP in the pediatric population in a cohort of pediatric patients prior to Covid-19 pandemic.